ASSESSMENT OF IRON STATUS AMONG SUDANESE MENOPAUSAL WOMEN - Allah, SihamKhalifaAbd; Mohamed, AbedelrahmanSyid; Mohmmed, AreegAlsail; Yassein, RaianBakhet; Alballah, NosibaAbdelmajid; Alseedig, Nada Omer (International Journal of Research -GRANTHAALAYAH, 2016)
Menopause is very important turning phase in the life of a female and is associated with hormonal changes. These hormones affect the overall personality however menopause is also associated with varied menopausal symptoms. Menopause women are a high risk group for iron level disturbance in your bodies. This was descriptive cross-sectional study aimed to determine the serum iron level in menopause women. Following informed consent, fifty subjects in menopause period, and sex matched fifty healthy premenopausal subjects as controls were enrolled. Serum iron was measured using spectrophotometer. Mean of serum iron level was significantly lower among menopause women when compared with the premenopausal women (control) (P.value 0.04). There was significant changing in serum iron level according to age duration (P.value 0.000). We observed changes in iron level between menopausal women when compared with premenopausal women, this study confirm iron deficiency among menopause women. Also observed that the level of serum iron decreased in certain age just after beginning menopausethen increased in certain age and return also to decrease with increased of age.